VISIONARY LEADERSHIP IN THE TRANSFORMATION OF ISLAMIC BOARDING SCHOOL MANAGEMENT - fatihatul karomah; Masduki Masduki; Siti Zulaikha (SOSIOEDUKASI, 2026)
Islamic boarding schools (pesantren), as the oldest Islamic educational institutions in Indonesia, currently face demands for management transformation in order to remain relevant to contemporary developments without losing their distinctive Islamic and traditional identity. This article aims to examine how visionary leadership contributes to the transformation of pesantren management, covering vision formulation, institutional restructuring, human resource development, digitalization, and organizational culture strengthening. This study employs a qualitative library research method, reviewing and synthesizing thirty-three prior studies published between 2018 and 2025, analyzed using content analysis based on three thematic categories. The findings indicate that the kiai's visionary leadership functions as a direction setter, change agent, spokesperson, and role model in realizing a more professional, transparent, and accountable transformation of pesantren management, while still preserving its Islamic and traditional values. The implication of this study is the importance of sustainable regeneration of visionary leadership so that pesantren can survive and thrive amid the dynamics of the digital era.